Direct ultrasound localisation for pleural aspiration: translating evidence into action. Issue 1 (January 2014) - Hannan, L. M.; Steinfort, D. P.; Irving, L. B.; Hew, M.
Abstract Background There is strong evidence that direct ultrasound localisation for pleural aspiration reduces complications, but this practice is not universal in Australia and New Zealand. Aims To describe the current utilisation and logistical barriers to the use of direct ultrasound localisation for pleural aspiration by respiratory physicians from Australia and New Zealand, and to determine the cost benefits of procuring equipment and training resources in chest ultrasound. Methods We surveyed all adult respiratory physician members of the Thoracic Society of Australia and New Zealand regarding their use of direct ultrasound localisation for pleural aspiration. We performed a cost‐benefit analysis for acquiring bedside ultrasound equipment and estimated the capacity of available ultrasound training. Results One hundred and forty‐six of 275 respiratory physicians responded (53% response). One‐third (33.6%) of respondents do not undertake direct ultrasound localisation. Lack of training/expertise (44.6%) and lack of access to ultrasound equipment (41%) were the most frequently reported barriers to performing direct ultrasound localisation. An average delay of 2 or more days to obtain an ultrasound performed in radiology was reported in 42.7% of respondents. Decision‐tree analysis demonstrated that clinician‐performed direct ultrasound localisation for pleural aspiration is cost‐beneficial, with recovery of initial capital expenditure within 6 months. Ultrasound training infrastructure is already available to up‐skill all respiratory physicians within 2 years and is cost‐neutral. Conclusion Many respiratory physicians have not adopted direct ultrasound localisation for pleural aspiration because they lack equipment and expertise. However, purchase of ultrasound equipment is cost‐beneficial, and there is already sufficient capacity to deliver accredited ultrasound training through existing services.